PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KEPRIBADIAN TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (Studi Pada Dinas Pertanian Dan Pangan Kabupaten Rembang ) - Kasiyadi, Agus; Soliha, Euis (Jurnal Ilmiah Telaah Manajemen, 2018)
This study aims to analyze the influence of leader member exchange (LMX) and personality on the performance of employees with motivation as a mediation variable at the Pertanian dan Pangan Rembang District. In this study the independent variable that affects the performance of employees in the limit only on the variable leader member exchange and personality with motivation as a variable mediation.Population and sample in this research is employee at Dinas Pertanian dan Pangan of Rembang, with total respondent amounted to 130 employees, with sampling using census method. The data testing techniques used include validity test with factor analysis, reliability test with alpha cronbach formula, multiple regression analyst, and test of determination coefficient significance to prove the hypothesis of the research, and to use the test of test for mediation test.The results of this study show that the ability of the model in explaining correctly influence leader member exchange, personality and motivation of 50.4% of the performance, while the rest of 49.6 in influenced by variables outside the model. From the result of the mediation effect can be known that the motivation variable proved to mediate perfect leader member exchange variable of 0.4179, and full mediate personality to the performance of 0.4715. Keywords: leader member exchange, personality, motivation, and performance